The Urgency of Dialogue with Children in Problem-Solving Efforts - Hufron, Muhammad; Attammi, Kholisna (Journal of Social Science and Education Research, 2024)
The purpose of this study is to find out the importance of dialogue with children and the obstacles in dialogue between parents and children. And understand how to have an effective dialogue to solve a problem. The method used is a literature method to analyze data about the purpose of this research. The results of the study show that there are still many parents who do not use the dialogue method in an effort to solve problems with their children. And parents tend not to listen to a child's complaints. This method of dialogue is very important in efforts to solve problems and find the right solution for both parties.